Shaping Teacher Identity through Microteaching: Experiences of Pre-Service EFL Teachers - Januari Rizki Pratama Rusman; Lina Aris Ficayuma; Nailul Author Restu Pamungkas (Universitas PGRI Semarang, 2026)
This present study aims to investigate how microteaching experiences construct pre-service EFL teachers' teacher identity particularly in private university contexts. Using a qualitative case study design, the participants of the research were composed of 34 pre-service teachers who took English-Language Education programs and participated in a microteaching course. Data collection included reflective journals, semi-structured interviews, classroom observations and document analysis and thematic analysis was used to analyze the data. Teacher identity was found to be constructed through an ongoing and multi-dimensional process characterized by the emergence of self-consciousness, the negotiation of confidence and anxiety, feedback matters, pedagogical beliefs and teaching practices, social interaction or contextual factors. Microteaching was commonly cited as both a site for practicing teaching skills and a space where identities are forged, contested, reflected upon and reformulated. Indeed, the study depicts reflective practice, collaborative learning and supportive feedback as their emerging themes to facilitate identity development. In contrast, the particular institutional situation and self-reported data limit your study. It is suggested that future research scope should encompass longitudinal and mixed-methods approaches to investigate the development of teacher identity across varying phases of teacher education and settings. This study adds to the growing body of literature surrounding teacher identity by offering a nuanced look at how microteaching plays a role in shaping pre-service EFL teachers’ professional identities.